Assessing School Management In Santa Theresia Kindergarten, Central Java - Ilham Prahesti, Swantyka; Yesi Wulandari, Aloysia; Kartika Dewi, Nufitriani; Tamtomo, Aryo; Restu Novia, Sih (KnE Social Sciences, 2022)
This study aims to determine the management of education in Santa Theresia Kindergarten. This study uses a descriptive method with a qualitative approach. The research subjects are principals, teachers, and parents. The subjects were selected through a purposive sampling technique. Data were analysed by systematically searching and structuring interview transcripts, recordings, photos, and documents. The results showed that the planning of educational programs at the Santa Theresia Kindergarten school, in general, has been well prepared. Additionally, the management organization in Santa Theresia Kindergarten, in general, has reflected a relevance between the abilities and skills of personnel and educational needs. Lastly, The implementation of education in Santa Theresia Kindergarten is directed at the learning process running well, effectively, and fun. In general, of the eight pre-set standards, several standards are doing well, namely financing standards, content standards, process standards, educators and education personnel standards, infrastructure standards, and financing standards. At the same time, the standard that requires more attention is the standard of assessment because teachers are not consistent in conducting the assessment Keywords: Kindergarten, School management, educational program